Real-time temperature and humidity monitoring of stingless bee colonies using IOT technology / Hajar Jaafar, Mohamad Taib Miskon and Muhd Azri Abd Razak - Jaafar, Hajar; Miskon, Mohamad Taib; Abd Razak, Muhd Azri (Faculty of Plantation and Agrotechnology, 2023)
This paper presents the development and testing of an Internet of Things (IoT)-based stingless bee monitoring system. The system consists of data loggers located at the stingless beehives, which use Arduino microcontrollers to measure the temperature and humidity within the hives. The data is transmitted wirelessly to an IoT gateway using Lora, and from there to a cloud database. A web-based user interface allows users to access and visualize the data in real-time. The methodology for this project involved the design and development of the system, and the system was tested over a 16-day period to evaluate its performance and reliability. The results showed that the system was successful in providing continuous, reliable monitoring of the temperature and humidity within the hives and has the potential to support the sustainable management and conservation of these important pollinators. Additionally, the system was able to withstand harsh outdoor environments during the test period, demonstrating its robustness and durability. The user interface was user-friendly and provided a convenient way to access and analyze the data. The system has the potential to be implemented in a variety of settings and could be a valuable tool for beekeepers and researchers alike.